Ann Miller her life and career - Shelley, Peter 1962- (McFarland & Company, Inc., Publishers, 2020)
"Ann Miller (1923-2004) was an American actress, dancer, singer and author. Best known as a tap dancer, Miller practiced other forms of dance, and some of her solo routines are considered as good as any recorded in film musical history. Despite a reputation as a kook who believed she was psychic, and the potentially flat image of a "glamour girl," Miller's wit, charm and genuine ability to act gave her and her characters depth. This biography presents Ann Miller's career in the context of her fascinating life. Her career began with child acting and included 3 Hollywood studio contracts, two retirements for marriage, and appearances in film, stage, variety shows, sitcoms and more. She made a comeback in the stage musical Sugar Babies, earning a Best Leading Actress in a Musical Tony Award nomination. She was even appointed an international spokesperson for MGM in the ailing years of the studio."-Provided by publisher"--
Keywords: Miller, Ann -- 1923-2004; Miller, Ann / 1923-2004; Motion picture actors and actresses / United States / Biography; Motion picture actors and actresses; United States; Biographies; Biografie